2019
DOI: 10.1021/acs.est.9b05379
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Desorption Mechanisms of Cationic and Zwitterionic Per- and Polyfluoroalkyl Substances in Natural Soils: Thermodynamics and Hysteresis

Abstract: Sorption linearity and reversibility are implicit in models for the fate and transport of per-and polyfluoroalkyl substances (PFAS). In this study, however, we found that the sorption of cationic and zwitterionic PFAS in natural soils was highly nonlinear. The nonlinearity was so severe that it led to a variation in the coefficient of sorption by several orders of magnitude over the experimental concentration range. This implies a considerable increase in sorption as concentration falls in the natural environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(141 citation statements)
references
References 89 publications
9
131
1
Order By: Relevance
“…The difference in PFAS leachability suggests that soil textural class may play a role and the sandy soils tend to leach out most of the PFAS (65%–99%) they retain. Whether such a trend can be generalized to other soils needs caution, as soil properties could greatly influence the desorption of nonanionic PFAS from soils (Nguyen et al, 2020; Schaefer et al, 2021; Xiao et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The difference in PFAS leachability suggests that soil textural class may play a role and the sandy soils tend to leach out most of the PFAS (65%–99%) they retain. Whether such a trend can be generalized to other soils needs caution, as soil properties could greatly influence the desorption of nonanionic PFAS from soils (Nguyen et al, 2020; Schaefer et al, 2021; Xiao et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The focus of this paper is the potential influence of precursor transformation on long-term PFOA fate and transport in groundwater, rather than comparative sorption isotherms. Though it is not the purpose of this paper to summarize the literature with respect to potential PFAS sorption complexities, useful summaries are provided in Wei et al (2017), Xiao et al (2019), Nguyen et al (2020), Zhou et al (2021), andSchaefer et al (2021). Consistent with previously cited PFAS modeling publications, our work assumed linear, equilibrium sorption/desorption.…”
Section: Limitationsmentioning
confidence: 98%
“…A previous study reported 83% of precursors measured through TOPA were zwitterionic/cationic at an AFFF-contaminated site and were highly retained on negatively charged soil (Adamson et al, 2020). Another study that examined the sorption behavior of the zwitterionic/cationic precursors with the soil associated their sorption mechanism with electrostatic interactions at low concentrations of precursors and hydrophobicity was considered as a poor predictor of sorption for zwitterionic/cationic precursors (F. Xiao et al, 2019). Even though anion exchange resin showed higher adsorption for PFAS and precursors from diluted AFFF solution than cation exchange resin, GAC, and non-ionic resin in laboratory batch studies, reduced adsorption was observed with zwitterionic and cationic precursors than anionic precursors (Fang et al, 2021).…”
Section: Removal Of Precursors Through the Poe Filtermentioning
confidence: 99%